2014
DOI: 10.1590/s1517-83822014000400036
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C-reactive protein in differantiating to contamination from bacteremia

Abstract: Procalcitonin (PCT) and C-reactive protein (CRP) are important biological markers used in the diagnosis of severe infections. The aim of this study was to evaluate the consistency of blood culture with PCT and CRP in differentiating contamination and non-bacteremia from true bacteremia. In this study blood samples were obtained from 809 febrile patients and analyzed using BACTEC 9120 system. All of positive blood cultures were performed Gram staining. The microorganisms were identified with conventional method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The biofilm assay revealed that 94.3% (33/35) of the isolated P. mirabilis strains are biofilm producers. Our findings are consistent with those reported by Kwiecinska-Piróg 48 . The biofilm is one of the most important virulence determinants of bacteria.…”
Section: Discussionsupporting
confidence: 94%
“…The biofilm assay revealed that 94.3% (33/35) of the isolated P. mirabilis strains are biofilm producers. Our findings are consistent with those reported by Kwiecinska-Piróg 48 . The biofilm is one of the most important virulence determinants of bacteria.…”
Section: Discussionsupporting
confidence: 94%
“…Several studies found that PCT showed good discrimination between BSI and contamination with an AUC of 0.86 [22, 24]. Additionally, in a PCR diagnostic (SeptiFast) test, a PCT value of <0.37 ng/ml had a 99% negative predictive value for this assay [25].…”
Section: Introductionmentioning
confidence: 99%
“…PCT is an important acceptable biomarker during severe bacterial infections and sepsis (13). PCT can be used in not only diagnosis of infection but also in predicting severity of the underlying disease, treatment response and results (14,15). It has been stated in the literature that use of PCT for these purposes is more specific than CRP (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported that PCT levels do not vary in presence of Gram negative and Gram positive agents, a larger number of studies have suggested that PCT levels increased more significantly in Gram negative infections (14). Inflammatory cascades are complicated processes in sepsis while Gram positive, Gram negative and fungal agents which play important roles in these processes may activate these cascades in distinct ways (16).…”
Section: Discussionmentioning
confidence: 99%